Pengembangan Desa Wisata Berbasis Agropolitan - Irianto, Heru; Nurany, Fierda (Universitas Tulungagung, 2024)
The development of agropolitan-based tourism villages emerged as an innovation that responds to problems related to social and economic challenges in rural communities. This dynamic involves a number of factors, including increasing awareness of the importance of environmental preservation and sustainability. Villages that are largely dependent on agriculture often face economic constraints, especially with limited economic diversification in the region. As a solution, the agropolitan-based tourism village concept integrates tourism and the agribusiness sector to stimulate local economic growth. The purpose of this study was to determine the development of agropolitan-based tourism villages in Wonosalam and the factors that hinder the development of agropolitan villages. This research method uses qualitative methods with SWOT analysis. The results of this study show that the importance of rural economic development through the agribusiness sector is a key element in agropolitan area policy. Support from the government and relevant institutions is an important factor to ensure the successful implementation of this policy, both in the form of financial assistance and policies that support the growth of the agribusiness sector. The success of agropolitan-based tourism villages in Wonosalam is not only related to economic growth, but also to the preservation of local culture and traditions. The success of agropolitan villages in Wonosalam involves optimizing internal strengths and mitigating weaknesses, by overcoming dependence on the agricultural sector through economic diversification. Dependence on government support needs to be balanced with strengthening local capacity so that agropolitan villages are more independent